Claudin-4-adhesion signaling drives breast cancer metabolism and progression via liver X receptor [beta] - Murakami-Nishimagi, Yuko; Sugimoto, Kotaro; Kobayashi, Makoto; Tachibana, Kazunoshin; Kojima, Manabu; Okano, Maiko; Hashimoto, Yuko; Saji, Shigehira; Ohtake, Tohru; Chiba, Hideki (Breast cancer research : BCR, 2023)
Background Cell adhesion is indispensable for appropriate tissue architecture and function in multicellular organisms. Besides maintaining tissue integrity, cell adhesion molecules, including tight-junction proteins claudins (CLDNs), exhibit the signaling abilities to control a variety of physiological and pathological processes. However, it is still fragmentary how cell adhesion signaling accesses the nucleus and regulates gene expression. Methods By generating a number of knockout and rescued human breast cell lines and comparing their phenotypes, we determined whether and how CLDN4 affected breast cancer progression in vitro and in vivo. We also identified by RNA sequencing downstream genes whose expression was altered by CLDN4-adhesion signaling. Additionally, we analyzed by RT-qPCR the CLDN4-regulating genes by using a series of knockout and add-back cell lines. Moreover, by immunohistochemistry and semi-quantification, we verified the clinicopathological significance of CLDN4 and the nuclear receptor LXR[beta] (liver X receptor [beta]) expression in breast cancer tissues from 187 patients. Results We uncovered that the CLDN4-adhesion signaling accelerated breast cancer metabolism and progression via LXR[beta]. The second extracellular domain and the carboxy-terminal Y197 of CLDN4 were required to activate Src-family kinases (SFKs) and the downstream AKT in breast cancer cells to promote their proliferation. Knockout and rescue experiments revealed that the CLDN4 signaling targets the AKT phosphorylation site S432 in LXR[beta], leading to enhanced cell proliferation, migration, and tumor growth, as well as cholesterol homeostasis and fatty acid metabolism, in breast cancer cells. In addition, RT-qPCR analysis showed the CLDN4-regulated genes are classified into at least six groups according to distinct LXR[beta]- and LXR[beta]S432-dependence. Furthermore, among triple-negative breast cancer subjects, the "CLDN4-high/LXR[beta]-high" and "CLDN4-low and/or LXR[beta]-low" groups appeared to exhibit poor outcomes and relatively favorable prognoses, respectively. Conclusions The identification of this machinery highlights a link between cell adhesion and transcription factor signalings to promote metabolic and progressive processes of malignant tumors and possibly to coordinate diverse physiological and pathological events. Keywords: Tight junction, Claudin, Cell adhesion signal, Nuclear receptor, Triple-negative breast cancer